USING SCRAMBLE LETTER GAME IN TEACHING ENGLISH AT FIFTH GRADE STUDENTS OF SDN TELUK DALAM 3 BANJARMASIN - Rusmi Saniti (ELTR Journal, 2017)
In teaching a language, a teacher should apply some strategies to all level. A good teaching strategy would automatically facilitate to get students interest in learning process and also it can improve students to motivate and achieve to learn English. It is scramble letter game, which is the technique to build words by work cooperative and competitive. Therefore, the researcher would like to find out whether the scramble letter game improves the student achievement in English subject. The research result shows that the effectiveness of using scramble letter game while teaching English has increased in experiment class with average score 60-70 however in the control class doesn’t achieve like the experimental class with average score 60. The use of scramble letter game is effective as technique while teaching English in SDN Teluk Dalam 3 Banjarmasin in Academic Year 2012/2013. Based on the the result, it is suggested that the scramble letter game can be used as one of the alternative and variation of their techniques in teaching and learning process.